Fatores e mecanismos que influenciam a resistência em soja a Anticarsia gemmatalis Hübner e Spodoptera frugiperda (J. E. Smith) - Souza, Bruno Henrique Sardinha de [UNESP] (2014)
The velvetbean caterpillar Anticarsia gemmatalis Hübner and the fall armyworm Spodoptera frugiperda (J. E. Smith) are two of the major defoliating pests of soybeans. Among the methods available for their control, the use of genotypes possessing moderate and high resistance stands out. However, numerous factors, inherent to the plant or to the insect, may influence the expression of resistance in plants. Thus, this work aimed to evaluate potential factors influencing the expression of resistance in soybeans, and we tested the hypotheses that flavonoids, nutrients, oxidative enzymes, phenolics, proteins, and proteinase inhibitors may be some of the mechanisms responsible for resistance to the velvetbean caterpillar and fall armyworm. Three experiments were performed in order to elucidate these issues. The first experiment evaluated the influence of the following factors on the expression of antixenosis in the resistant genotype IAC 100 and susceptible genotype BRSGO 8360 to both insects in free-choice and no-choice feeding assays: one larva versus two larvae per leaf disc; use of non-starved larvae versus larvae starved for three hours prior to the assay; leaf disc versus entire leaflet; upper part versus lower part of plants; vegetative growth stage versus reproductive stage. The second experiment assessed the influence of the upper part versus lower part of the plant, and plants at vegetative growth stage versus reproductive stage on the expression of antibiosis to A. gemmatalis and S. frugiperda in the resistant genotype PI 227687 and susceptible genotype IGRA RA 626 RR. In addition, the concentration of nutrients and flavonoids were evaluated as potentital mechanisms responsible for resistance in soybeans. The macronutrientes quantified in the leaves of the soybean genotypes from the respective treatments were N, P, K, Ca, Mg, and S; the quantified micronutrients were B, Cu, Fe, Mn, and Zn; among the flavonoids, we quantified ...